ANALYSIS OF STUDENT’S CRITICAL THINKING IN WRITING ARGUMENTATIVE ESSAYS - Efendi, Nasori (IJLECR (International Journal of Language Education and Cultural Review), 2018)
The purpose of this qualitative study is to investigate, classify, and analyse critical thinking in student’s writing argumentative essays. The method used in this research is qualitative content analysis using the approach of Facione’s (2009) holistic critical thinking scoring rubric (HCTSR). Data collection technique used in this study is by document observation of English education department students’ blog-texts about teacher’s welfare in Indonesia, in one of private universities in West Jawa, Indonesia. Data obtained are from students’ writing emails submissions tasks; then, the data are analyzed by the researcher qualitatively based on coding frame document of writing. The results of this study indicate that in the the level of student’s critical thinking in writing varies demonstrated by the students.